Holography with photoelectrons: A direct approach - Steinrück, Hans-Peter; Zharnikov, Michael (Journal of Physics: Condensed Matter, 2001)
This article reviews the work performed by the authors regarding photoelectron holography on clean metal surfaces and simple adsorbate arrangements. The following systems were investigated: Pt(1 1 0)-1 × 2, Ni(1 1 0), Ni(1 1 1), Ni(1 1 0)-c(2 × 2) S, Ni(1 1 1)-p(2 × 2) S and Ni(1 1 1)-(5√3 × 2) S. The photoelectron diffraction patterns, which are interpreted as holograms, were recorded using synchrotron radiation at the German synchrotron facility BESSY-I in Berlin. For most systems these holograms were acquired at various kinetic energies. The real space structures were reconstructed from these data using the single wave number as well as the multiple wave number algorithm, without any prior assumptions. It was demonstrated that the local geometrical structure of clean single crystal surfaces and of adsorbate systems can be successfully reconstructed by using photoelectron holography with some restrictions.